PENINGKATAN PERMURNIAN MUTU MINYAK KEMIRI DENGAN ADSORBSI BENTONIT - Sariyusda Sariyusda (University of Muhammadiyah Jakarta, 2017)
This purification tool is an alternative technology to purify the hazelnut oil by utilizing natural bentonite as an adsorbent. The type of adsorption tool is a type of fixed bed coloums (vertical cylinder), which the column is equipped with bentonite adsorbent bed. This hazelnut oil purification tool is designed with a capacity of 5 liters. Designed material using PVC pipe as high as 160 cm, while for media column adsorber made of acrylic 2 inc as 30 cm in diameter average of 50 mm, Bentonit as adsorbent filled into column as high as 80 cm. Adsorber is also equipped with a fine filter media at the top and bottom. To circulate the candlenut oil continuously the adsorber is equipped with a low pressure pump. Bentonite size 10 mesh, 20 mesh and 30 mesh burned in furnace reach 300 0C temperature then activated with H2SO4 1 M by immersion. After rinsing with aquadest bentonite dried in an oven at 110oC. To analyze the performance of the adsorber was performed the operation of the equipment by analyzing the samples at circulation time 15, 30, 45, and 60 minutes. From the results of the study the longer the circulation time (60 minutes) and the size of bentonite particles as the adsorbent getting smaller (30 mesh), the resulting candlenut oil more pure. Refractive index of 1.474, Weight of type 0,92443 and calorific value 33786. The yield of kemiri oil using natural bentonite adsorbent in accordance with SNI quality standard 01-4462-1998.